The Role of Finasteride in the Management of Androgenetic Alopecia in Male: A Narrative Review - Tumkur, Anil; Cher Ern, Charmine Caryn Teo; Shuang, Chang Ching; Yong, Amilia Chai Hui; Yee, Chan Poh; Leen, Chai Tze; Lock, Lee Kah; Singh, Nermesh (Indian Journal of Pharmacy Practice)
The purpose of this review was to evaluate the role of finasteride, a type-II 5α-reductase inhibitor in the prevention and treatment of androgenetic alopecia (AGA) in males. Finasteride inhibits 5α-reductase and reduce the biosynthesis of dihydrotestosterone (DHT). This inhibition marks a decrease in concentration of DHT and provides a novel and selective approach to androgen deprivation. Clinical trials have proven the safety and efficacy of tablet finasteride 1 mg for AGA. In this review, we discuss all aspects of finasteride, including dosing and indication, pharmacology, pharmacokinetics to its role in the treatment of AGA.
Keywords: Androgenic alopecia; DHT; Finasteride; Norwood-Hamilton scale; Safety.